Diagnostic challenges in critical care management of fluid and electrolyte disturbances in a poor-resource setting: a survey of critical care doctors - Imoh, Lucius C.; Okoye, Onyedika G.; Abimiku, Audu C.; Abu, Alex O.; Asorose, Solomon A.; Echebiri, Promise O. (International Journal of Research in Medical Sciences, 2017)
Background: To determine the challenges in diagnostic support for adequate fluid and electrolyte (F/E) management in a poor-resource critical care setting. Methods: This cross-sectional survey was conducted between March and May 2017 in one hundred and four (104) doctors practicing in four tertiary hospitals in North-central Nigeria. These doctors were currently working in Accidents and Emergency Units (A/E), Intensive care Units (ICU) and Children Emergency Units and have worked for at least two months prior to the study. They were given a structured questionnaire to fill and return. The questionnaire among other things, addressed laboratory-related factors that affect management of F/E disturbances. Results: Unavailability of some laboratory tests, inaccuracy of laboratory results, incomplete test results and delay in obtaining results, hampered F/E management in critical care according to more than 75% of the surveyed doctors. About sixty percent of the doctors reported a turnaround time (TAT) of ≥3 hours for electrolytes and most emergency biochemical tests (except urine dipstick and Blood gases). Also ≤25% of doctors responded that electrolytes and most emergency biochemical tests (except urine dipstick and Blood gases) were offered in the ICU/Emergency unit laboratories. Ten percent or less of doctors reported that electrolytes and the emergency biochemical test were available by Point of care testing (POCT). Conclusions: There is an urgent need for the managers of healthcare in LMICs to establish functional laboratories in ICUs, explore the use of POCT and build capacity for diagnostic critical care.